Baicalin suppresses Propionibacterium acnes-induced skin inflammation by downregulating the NF-κB/MAPK signaling pathway and inhibiting activation of NLRP3 inflammasome - Fang,Fang (2020)
Acne is a kind of common, chronic skin condition caused by the inflammation of the sebaceous glands in hair follicles. Recent studies have demonstrated that baicalin (BA) possesses potential anti-inflammatory properties. In this study, we evaluated the anti-inflammatory activity of BA in vitro and in vivo. Heat-killed Propionibacterium acnes-induced THP-1 cells and live P. acnes-injected male Sprague Dawley rats were used for establishing the acne model. The rate of ear swelling was calculated, and the severity was determined by hematoxylin and eosin staining. The production of cytokines [interleukin (IL)-1β, IL-6, IL-8, and tumor necrosis factor (TNF-α)] in the cell supernatant and ear tissue homogenates was measured by ELISA. Protein levels of JNK, ERK, P38, IκBα, P65, Nod-like receptor pyrin domain-containing 3 (NLRP3), pro-caspase-1, and IL-1β in THP-1 cells and ear tissues were detected by western blotting. NLRP3 and IL-1β were detected by immunohistochemistry, and the NLRP3, IL-1β and pro-caspase-1 mRNAs were detected by quantitative real-time polymerase chain reaction (qRT-PCR). The results showed that BA decreased the expression of pro-inflammatory cytokines in vitro and in vivo. Moreover, BA down-regulated the phosphorylation of JNK, ERK1/2, and κBα and inhibited the nuclear translocation of p65. Furthermore, BA inhibited the activation of NLRP3 inflammasome, at both the gene and protein levels. Taken together, the results demonstrated that BA might exert its anti-inflammatory activity by inhibiting NF-κB/MAPK signaling pathways and consequently suppressing the activation of the NLRP3 inflammasome both in vivo and in vitro.